Workload and salary as determinants of pedagogical graduates’ employment by occupation - L. M. Nurieva; S. G. Kiselev (Obrazovanie i Nauka, 2021)
Introduction. The problem of the effectiveness of the pedagogical education system remains one of the most discussed topics in modern professional discourse. A large proportion of leaders of the educational industry and representatives of the expert community are convinced that graduates of pedagogical universities and colleges are not sufficiently prepared for independent professional activity and deflect from work in their field. The refusal of graduates to be employed by occupation is associated mainly with the poor quality of students’ practical training in universities. Criticising the low attendance rates of young professionals in schools, analysts often ignore the conditions of employment in educational institutions. Meanwhile, the appearance of a new form of statistical observation of OO-1 and OO-2 on open access makes it possible not only to track the results of employment of graduates of the vocational education system in schools across the country, but also to compare them with the conditions for hiring: the current workload on staff and the level of teachers’ salaries.The aim of the present research was to find the dependence of the results of pedagogical graduates’ employment by occupation on the conditions of employment in schools: the level of teachers’ salaries and workload in the regions of Russia.Methodology and research methods. The research methodological framework is a structural approach based on applied research procedures (observation, description, comparison, counting, measurement, modelling, etc.), according to which general scientific (comparative, retrospective analysis, systematisation, generalisation) and statistical research methods (statistical and correlation analysis, etc.) were employed. The analysis of official documents of educational authorities of different levels and educational institutions, scientific publications and forms of federal statistical observation of OO-1 and OO-2 was conducted. The processing of regional educational statistics was carried out using the Online Analytical Processing technology, which makes it possible to obtain OLAP cubes and form analytical slices in accordance with emerging research tasks. The slices were studied in detail using the Analysis ToolPak addin procedures and the statistical functions of the Excel library. In the course of the analysis, the authors performed the calculation of measures of the statistical relationship between the studied variables and their graphic visualisation.Results. This study established a high level of pedagogical labour market segmentation by territorial and qualification-age criteria of employees. The effects of influence on the part of state and public institutions and practices, leading to systematic discrimination of certain groups of educators, were revealed. Regional data provide the examples of discrimination against young teachers in remuneration, both in the process of employment due to the lack of qualification grades, and in the process of work, as a consequence of the inaccessibility to payments from the incentive part of the salary fund of schools. It is shown that the improvement of the results of pedagogical graduates’ employment by occupation is related to the improvement of the wage system, increasing the base rates and reducing the intra-industry differentiation of earnings among workers of different ages.Practical significance. The authors are convinced that this article will clarify the approaches for adjusting the mechanism for distributing the wages fund of schools, develop measures to attract young people to teaching and ensure the elimination of the shortage of personnel in the education system.